Khamir Antagonis untuk Pengendalian Penyakit Antraknosa pada Buah Avokad Selama Penyimpanan - Yuli Fitriati; Suryo Wiyono; Ivone Oley Sumarauw (The Indonesian Phytopathological Society (Perhimpunan Fitopatologi Indonesia), 2013)
Anthracnose caused by Colletotrichum gloeosporioides is an important disease in avocado fruit during storage. An effective, cheap, and safe control method is necessary as an alternative to subtitute the use of fungicides in postharvest disease control. This research aimed to identify yeast antagonist from avocados that are effective in controlling anthracnose disease on avocado fruit. Research was started with isolation of C. gloeosporioides and yeast from avocado fruit, followed by in vivo bioassay, antibiosis assay, and chitinolitic activity assay. In vivo bioassay was done by dipping avocado fruit on yeast cell suspension. As many as 23 yeasts isolates was obtained from avocado fruits. Eight yeast isolates (A28, A32, A33, A34, A35, A36, A37, A38) showed very effective for inhibiting anthracnose disease in avocado fruit at concentration of 106 mL-1 and 107 mL-1. However, only four isolates were chosen for further characterization based on morphological and molecular identification. Two species of yeast was identified as Pichia anomala, i.e. isolates A33 and A37 and Candida intermedia, i.e. isolates A35 and A36.